Ewolucja roli sekundantów w kodeksach honorowych Władysława Boziewicza 1919-1927 - Byczyński, Marcin (Oficyna Wydawnicza Epigram, 2024)
Niniejszy artykuł poświęcony jest kluczowym osobom w postępowaniu honorowym – sekundantom, którzy zwani byli również zastępcami honorowymi. Poprzez dokonanie analizy porównawczej kodeksów honorowych Włdysława Boziewicza Polskiego kodeksu honorowego (1919)oraz Ogólnych zasad postępowania honorowego (1927) dokonana ostanie rekonstrukcja zawartej w nich normatywności w zakresie roli sekundantów. Pozwoli to prześledzić kierunek zmian w refleksji Boziewicza nad istotą przebiegu postępowania honorowego, która zawarta jest w jego kodyfikacjach. Tym samym ujawni się jeden z punktów jego krytyki społecznej wymierzonej względem praktyki postępowań honorowych. Badanie ujawni jak w refleksji Boziewicza nad postępowaniami honorowymi wzrosła rola autonomicznej refleksjimoralnej zastępców honorowych i wspólnoty etycznej, którą reprezentują, względem woli ich mocodawców. This article is devoted to the key persons in honour proceedings - the seconds, who were also known as honorary deputies. Through a comparative analysis of Wladyslaw Boziewicz’ s codes of honour, the Polish Code of Honour (1919) and General Rules of Honorary Conduct (1927), a reconstruction will be made of the normativity of the role of seconds contained in them. This will allow us to trace the direction of changes in Boziewicz ’ s reflection on the essence of the course of honour proceedings, which is contained in his codifications. Thus, one of his points of social criticism directed against the practice of honour proceedings will be revealed. The study will demonstrate how, in Boziewicz ’ s reflection on honour proceedings, the role of autonomous moral reflection of honour deputies and the ethical community they represent has increased in relation to the will of their principals.
Evolution of the Role of Seconds in the Codes of Honour by Władysław Boziewicz 1919-1927
Authors english translation is availible here: Byczyński, M. J. (2024, February 24). Evolution of the role of seconds in the codes of honour by Wladyslaw Boziewicz 1919-1927. https://doi.org/10.31235/osf.io/fwjpx
Keywords: honor; honour; honour code; honor code; seconds; honor deputies; honour deputies; zastępcy honorowi; sekundanci; Władysław Boziewicz; Wladyslaw Boziewicz; honour representatives; honor representatives; Alternative Dispute Resolution; ADR; ethics; morality; philosophy; philosophy of honour; philosophy of honor; polska tradycja honorowa; filozofia honoru; kodeksu honorowe; polskie kodeksu honorowe; Polski Kodeks Honorowy; ogólne zasady postępowania honorowego; dwudziestolecie międzywojenne